Rethinking the Plant Economics Spectrum for Annuals: A Multi-Species Study - Kurze, Susanne; Engelbrecht, Bettina M. J.; Bilton, Mark C.; Tielbörger, Katja; Álvarez-Cansino, Leonor (Frontiers in Plant Science, 2021)
The plant economics spectrum hypothesises a correlation among resource-use related traits along one single axis, which determines species’ growth rates and their ecological filtering along resource gradients. This concept has been mostly investigated and shown in perennial species, but has rarely been tested in annual species. Annuals evade unfavourable seasons as seeds and thus may underlie different constraints, with consequences for interspecific trait-trait, trait-growth and trait-environment relations. To test the hypotheses of the plant economics spectrum in annual species, we measured twelve resource-use related leaf and root traits in 30 winter annuals from Israel under controlled conditions. Traits and their coordinations were related to species’ growth rates (for 19 species) and their distribution along a steep rainfall gradient. Contrary to the hypotheses of the plant economics spectrum, in the investigated annuals traits were correlated along two independent axes, one of structural traits and one of carbon gain traits. Consequently, species’ growth rates were related to carbon gain traits, but independent from structural traits. Species’ distribution along the rainfall gradient was unexpectedly neither associated with species’ scores along the axes of carbon gain or structural traits nor with growth rate. Nevertheless, root traits were related with species’ distribution, indicating that they are relevant for species’ filtering along rainfall gradients in winter annuals. Overall, our results showed that the functional constraints hypothesized by the plant economics spectrum do not apply to winter annuals, leading to unexpected trait-growth and trait-rainfall relations. Our study thus cautions to generalize trait-based concepts and findings between life history strategies. To predict responses to global change, trait-based concepts should be explicitly tested for different species groups.